Analisis Kebutuhan Aplikasi Learning Manajemen System untuk Mapel Pendidikan Agama Islam pada Sekolah di Jawa Tengah - Moch. Mu'izzuddin M.Ag (Balai Diklat Keagamaan Semarang, 2022)
This reseacrh presents the following research problems: 1) The extent to which the use of learning applications in Islamic Religious Education (PAI) subjects in Central Java Province by PAI teachers in learning long distance; 2) obstacles faced by PAI subject teachers in distance learning; 3) the formulation of learning media needed by PAI teachers in implementing distance learning of Islamic Religious Education subjects.This research is a mixed quantitative and qualitative research. The description of the results of the quantitative research was confirmed by qualitative data collection to obtain the depth of answers from the quantitative results. Quantitative research sample selection technique is done by purposive sampling technique. Quantitative data collection techniques are carried out using a questionnaire or questionnaire instrument. Quantitative data were analyzed using descriptive analysis techniques to obtain an overview of the results of the research. Furthermore, the results of quantitative research were confirmed to the respondents with a qualitative approach, through interview techniques, and document analysis. Testing the validity of the data and sources is done by using triangulation technique. Processing of qualitative research data is processed with an interactive analysis model, which includes the stages of data collection, data reduction, data presentation and drawing conclusions. The results showed that 1) in general PAI teachers have used learning media as learning resources in the distance learning process, but they are still less varied. The media used by Islamic Religious Education teachers is still limited to the use of the whatsapp application which displays short text messages, images, videos, which are not constructed; 2) Constraints faced by Islamic Religious Education teachers in implementing distance learning in general are limited skills in using digital learning applications. On the other hand, Islamic Religious Education teachers who have used learning management system facilities, admit that the learning management system used is only effective for achieving cognitive competence, so that the achievement of competence in the affective aspect and competence in the psychomotor aspect of students has not been touched: 3) Digital learning applications What is needed to be developed in learning Islamic Religious Education remotely is a specific Learning Management System (LMS) application to achieve 3 domains of student competence, namely cognitive, affective, and psychomotors..